Klasifikasi Penempatan Siswa di Sekolah Menengah Atas menggunakan Metode Extreme Learning Machine - Akmal Subakti Wicaksana; Budi Darma Setiawan; Candra Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Placement of majors is one of the actions that can support the ability and motivation of student learning. Placement of the department itself has several factors that are used as considerations to determine the majors according to the abilities and interests of students. Factors used in determining majors between student psychological test results, report card grades for junior high school, BK evaluation, student interest, and parents' interests. Efficient it is not efficient. In the process of validation, the results of department placement are needed for 1 semester by looking at student learning outcomes data. In the placement of majors a system is needed that can help in classifying students' majors quickly and accurately, can be adjusted to the completion time of majors and errors in the arrangement of majors that are not in accordance with the interests and abilities of students. In this study using the Extreme Learning Machine method in grouping majors in high school students. In applying the ELM method the classification results obtained with the best average value of 98% using 14 features. To transfer data, practice and test the data used is 80:20, and the weight value is changed [-1,1], the value is biased with a range of [0,1], and use the activate sigmoid function.